Contribuições para o projeto de grooming de tráfego sobre redes ópticas WDM - Resendo, Leandro Colombi (2016)
Submitted by Maykon Nascimento (maykon.albani@hotmail.com) on 2016-05-17T20:09:39Z No. of bitstreams: 2 license_rdf: 23148 bytes, checksum: 9da0b6dfac957114c6a7714714b86306 (MD5) Tese Leandro Colombi.pdf: 1600437 bytes, checksum: d40bc605230b5d5995a431dc205d03a6 (MD5)